(untitled) (Biological Sciences - PJSIR, 2005)
. A mathematical model, which is based on the simultaneous interfacial chemical reactions and diffusion processes, is developed for the extraction of zinc ions from sulphate solution by di(2-ethylhexyl) phosphoric acid in n- heptane diluent. Actual column heights were compared with the predicted ones, using the design algorithm based on chemical kinetics. The experimental values of mass transfer coefficients could be varied and were in the range of industrial interest. Using the physicochemical data, hydrodynamics, mass transfer coefficient parameters and reaction kinetics pertaining to the system, it was possible to predict the interfacial flux and column height from first principles with a reasonable degree of accuracy.